Eksplorasi tradisi melengkan dalam pernikahan adat Gayo di Aceh Tengah - Razali, Razali; Sundana, Lina; Ramli, Ramli (Universitas Mulawarman, 2024)
This research aims to reveal the tradition of “melengengan” in the context of Gayo ethnic weddings in Central Aceh. The method used in this research is qualitative with a descriptive approach. Data was collected through in-depth interviews, participant observation and literature study. The findings of this research describe the process of implementing the “melengengan” tradition in Gayo ethnic wedding ceremonies, as well as identifying the meaning and important role of this tradition in Gayo ethnic culture and society. The role of the “melengengan” tradition in Gayo tribal culture is very important because it is one of the main pillars in maintaining and preserving their culture. In the midst of globalization and modernization, preserving this tradition is crucial in maintaining the identity and values of the Gayo tribe. The tradition of bowing is not only a symbol of marriage, but also a symbol of togetherness, honor, and solidarity among the Gayo ethnic community.